What Kind of Relation and Function Worksheet Based Tri-N Improve Critical Thinking Skills? - Widodo, Sri Adi; Wulandari, Ika; Ayuningtyas, Annis Deshinta; Pusporini, Widowati; Kusuma, Dianne Amor; Dwipriyoko, Estiyan (UNNES JOURNAL, 2025)
Mathematical critical thinking skills have so far shown unsatisfactory results, so media or learning resources such as worksheets are needed to complete them. In addition, concepts of scientific learning such as Niteni, Nirokke, and Nambahi activities have not provided opportunities for students to think critically. For this reason, this study aims to obtain valid and practical relations and function worksheets based on tri-n. The research stages used are defining, designing, and developing. These three stages are part of the development research with 4D. At the defining stage, data collection techniques use documentation to make the data analysis qualitative. At the design stage, data collection techniques use observation to make the data analysis qualitative descriptive. In the developing stage, the data collection technique uses a questionnaire, so the data analysis is quantitative. The results showed that the relations and function worksheets based on Tri-N had a V-Aiken index of more than 0.83, and some students responded well to this worksheet. Apart from that, the mathematics material in this Student Worksheet uses the Tri-N stages, namely Niteni, Nirokke, and Nambahi. Based on this, it can be concluded that the Tri-N-based Student Worksheet on Relations and Functions is a valid and practical result of development. For this reason, this worksheet can be used to improve students' critical thinking skills. Abstrak Kemampuan berpikir kritis matematis siswa selama ini menunjukkan hasil yang belum memuaskan, sehingga dibutuhkan media atau sumber belajar sepert worksheet untuk menyelesaikannya. Selain itu, konsep pembelajaran saintifik seperti kegiatan Niteni, Nirokke, Nambahi belum memberikan kesempatan kepada siswa untuk berpikir kristis. Untuk itu penelitian ini bertujuan untuk memperoleh Lembar Kerja Siswa Relasi dan Fungsi berbasis Tri-N yang valid dan praktis. Tahapan penelitian yang digunakan adalah mendefinisi, mendesain, dan mengembangkan. Ketiga tahapan ini merupakan bagian dari penelitian pengembangan tipe 4D. pada tahap mendefinisi, Teknik pengumpulan data menggunakan dokumentasi, sehingga analisis data yang digunakan bersifat kualitatif. Pada tahap mendesain, Teknik pengumpulan data menggunakan observasi, sehingga analisis data yang digunakan bersifat kualitatif deskriptif. Tahap mengembangkan, Teknik pengumpulan data menggunakan angket, sehingga analisis data yang yang digunakan bersifat kuantitatif. Hasil penelitian diperoleh bahwa Lembar Kerja Siswa Relasi dan Fungsi memiliki indeks V Aiken lebih dari 0,83, dan sebagian siswa memberikan respon sangat baik terhadap prototipe worksheet ini. Selain itu, materi matematika yang ada pada Lembar Kerja Siswa ini menggunaan tahapan Tri-N, yaitu Niteni, Nirokke, dan Nambahi. Berdasarkan hal tersebut dapat disimpulkan bahwa Lembar Kerja Siswa Relasi dan Fungsi berbasis Tri-N hasil pengembangan yang valid dan praktis. Untuk itu dimungkinkan worksheet ini digunakan sebagai salah satu cara untuk meningkatkan kemampuan beprikir kritis siswa.